Smart edible films based on gelatin and curcumin - Musso, Yanina Soledad (2016)
This work studied the preparation of edible smart films based on gelatin and curcumin. Films were prepared by casting using water and an ethanol-water mixture as solvents. The addition of curcumin, besides affecting the physicochemical properties of gelatin films, colored them depending on the pH of the film-forming dispersion (yellow at pH=6 and red at pH=11). It also provided films with important antioxidant properties, but no antimicrobial activity. The response of these materials against pH changes was evaluated simulating their contact with liquid and semisolid foods, and with a container headspace at acid and alkaline pH. In all tests, gelatin films with curcumin added could modify their color after being in contact with media of different pH. The use of an ethanol-water mixture as solvent was a good alternative to intensify film color and the visualization of their response capacity against pH changes, as well as to increase the antioxidant properties and hydrophobicity of films. These edible films could be used as smart food packaging, since they could inform consumers if the product was suitable for consumption through their capacity to sense pH changes.